2016
DOI: 10.1016/j.bbrc.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant human dihydroxyacetonephosphate acyl-transferase characterization as an integral monotopic membrane protein

Abstract: Although the precise functions of ether phospholipids are still poorly understood, significant alterations in their physiological levels are associated either to inherited disorders or to aggressive metastatic cancer. The essential precursor, alkyl-dihydroxyacetone phosphate (DHAP), for all ether phospholipids species is synthetized in two consecutive reactions performed by two enzymes sitting on the inner side of the peroxisomal membrane. Here, we report the characterization of the recombinant human DHAP acyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Supportive of the idea that these amino acids are involved in lipid binding is that human GNPAT missing the first 135 amino acids (Δ135GNPAT) is unstable, prone to aggregation, and loses enzymatic activity. 46 Further, we find in the amino terminus region of Xenopus Gnpat two amphipathic helices that are conserved in the human GNPAT ( Fig. 8 B).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Supportive of the idea that these amino acids are involved in lipid binding is that human GNPAT missing the first 135 amino acids (Δ135GNPAT) is unstable, prone to aggregation, and loses enzymatic activity. 46 Further, we find in the amino terminus region of Xenopus Gnpat two amphipathic helices that are conserved in the human GNPAT ( Fig. 8 B).…”
Section: Discussionmentioning
confidence: 62%
“…No other conserved lipid binding domains or motifs could be identified within Gnpat. The amino end of human GNPAT is suggested to be responsible for binding to membranes, 46 but this has not been demonstrated. Xenopus and human GNPATs display 76% similarity and 58% identity with high conservation in the N-end regions encoded by exons 2 and 3 ( Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Both enzymes are localized on the luminal side of the peroxisomal membrane (de Vet E. C. et al, 1997;Thai et al, 1997;Braverman and Moser, 2012) and may exist as a heterotrimeric complex in a 2:1 ratio of GNPAT to AGPS (Biermann et al, 1999;Piano et al, 2016).…”
Section: Ether Lipid Biosynthesis: the Core Peroxisomal Pathwaymentioning
confidence: 99%
“…Studies involving patients deficient in either GNPAT or AGPS revealed a dependence on the presence of the catalytically competent AGPS for the stability and maximal activity of GNPAT ( Itzkovitz et al, 2012 ), leading to the hypothesis that the two enzymes form a functional complex in order to channel 1-acyl-DHAP from GNPAT to AGPS. Both enzymes are localized on the luminal side of the peroxisomal membrane ( de Vet E. C. et al, 1997 ; Thai et al, 1997 ; Braverman and Moser, 2012 ) and may exist as a heterotrimeric complex in a 2:1 ratio of GNPAT to AGPS ( Biermann et al, 1999 ; Piano et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%